Determination of Pesticides in Fruits by Gas Chromatography/Mass Spectrometry after High Performance Gel Permeation Clean up - HADIAN, ZAHRA; HOSSEIN AZIZI, MOHAMMAD; HOSSEINY, HEDAYAT; KHOSRAVI-DARANI, KIANOUSH (Asian Journal of Chemistry, 2010)
An analytical method was used for the determination of 115 multiclass pesticides in fruits by gas chromatography/mass spectrometry. The occurance of 115 pesticides were assessed in 30 samples (melon, maskmelon and watermelon) collected in Tehran during year 2005. Extraction of the pesticides were carried out with ethyl acetate and the extract was cleaned up and concentrated by high performance gel permeation chromatography (HPGPC). Pesticide residues were identified and quantified using ion trap gas chromatography mass spectrometry detector. One of these pesticides was detected in samples at level of 0.02-0.07 mg/kg. The recovery levels of 115 pesticides from melon, maskmelon and watermelon were in the range of 60-140 % and the relative standard deviation values of the pesticides were less than 5 %. The recovery indicated that the described multiresidue procedure is an efficient and reliable tool for monitoring pesticide residues in fruits and HPGPC clean up technique effectively removed sample matrices without pesticide loss. The data demonstrated that the samples analyzed did not contain residues of the monitored pesticides above the accepted maximum residue limits (MRLs) as adapted by the FAO/WHO Codex Alimentarius Commission.